Realizing a Smart Supply Chain through the Triple-A Approach - Budi, Hasiun; Nailul, Muhammad (West Science Journal Economic and Entrepreneurship, 2025)
The increasing volatility of global markets has intensified the need for supply chains that are both technologically advanced and strategically resilient. This study conducts a literature review of 40 scholarly documents sourced from Google Scholar to examine how the Triple-A approach—Agility, Adaptability, and Alignment—can be leveraged to realize a smart supply chain. The review synthesizes theoretical frameworks, empirical studies, and case-based evidence across multiple industries, highlighting the interplay between digital technologies and Triple-A capabilities. Findings reveal that agility enables rapid responsiveness through real-time analytics and flexible operations, adaptability ensures long-term competitiveness via structural flexibility and continuous innovation, and alignment harmonizes stakeholder objectives through transparent communication and shared metrics. The integrated application of these three dimensions enhances supply chain resilience, sustainability, innovation capacity, and customer satisfaction. However, persistent challenges include measurement difficulties, change management resistance, and data interoperability issues. The paper concludes that realizing a smart supply chain requires a balanced development of Triple-A capabilities, strong leadership commitment, and continuous technological integration.